The New Space Race: China vs. USA - Seedhouse, Erik (Space Exploration,, 2010)
The world's most populous nation views space as an asset, not only from a technological and commercial perspective but also from a political one. The repercussions of this ideology already extend far beyond Washington. China vs. the United States explores future Chinese aspirations in space and the implications of a looming space race. Dr. Seedhouse provides background information on the fifteen-year history of the China National Space Administration and its long list of accomplishments. Sino-U.S. technological and commercial interests in space are discussed, including their interest in encouraging a potential space race. The national security objectives of the U.S. and China are also examined. .